1st International Conference on 3D Materials Science, 2012 Conference Proceedings - De Graef, Marc.; Friis Poulsen, Henning; Lewis, Alexis; Simmons, Jeff.; Spanos, George; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Addressing a critical growth area in materials science, this volume features papers presented at the 2012 International Conference on 3D Materials Science, organized by The Minerals, Metals & Materials Society (TMS). With the top researchers in the world assessing the state-of-the-art within the various elements of three-dimensional materials science, this collection provides the premier forum for authoritative presentations on all aspects of the science, including characterization, visualization, quantitative analysis, modeling, and investigation of structure-property relationships of materials.
Keywords: Building materials; Materials -- Analysis; Materials; Structural Materials; Characterization and Analytical Technique; Materials Engineering